ISLAMIC ACCOUNTING REPORTING PRINCIPLES AND FINANCIAL PERFORMANCE OF MSMEs IN NIGERIA. (Journal of the Management Sciences, 2024)
Despite Micro, Small and Medium Enterprises MSMEs being important agent of economic growth and are regarded as conduit of supply of human capital, innovations and technological advancement. Its evidence that many of these MSMEs, languish in low productivity, inadequate management and most importantly inadequate access to finance and loan facilities. The aim of this study is therefore to seek the effect of Musharakah, Mudarabah and Murabah on financial performance of MSMEs in Nigeria. The study employed a survey research design. A total 100 copies of questionnaire were distributed to customers of Jaiz bank. Data collected were analyzed using descriptive statistics to test the significance of the explanatory variables (Musharakah, Mudarabah and Murabah). The findings of the study revealed a significant increase of business market share which had a mean of 2.19 and standard deviation of 1.066 and implementing Musharakah interest free loans allowed enterprise to obtain a competitive edge. The Murabah also affected the growth of MSMEs through reduced interest rate which had a mean of 2.11 and standard deviation of 0.98. The study concluded that management team of MSMEs is able to improve the financial performance and increased market competitiveness of MSMEs. The study therefore recommended that the policy of Islamic accounting principles be upheld for better performance in achieving intended goals of MSMEs
Keywords: Musharakah, mudarabah, murabah, islamic accounting principles, reporting